Differentiation of division I (cfiA-negative) and division II (cfiA-positive) Bacteroides fragilis strains by matrix-assisted laser desorption/ionization time of-flight mass spectrometry - Nagy Erzsébet; Becker Simone; Sóki József; Zsoldiné Urbán Edit; Kostrzewa Markus (2011)
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is increasingly used in clinical microbiological laboratories to identify bacteria and fungi at a species level and to subtype them. The cfiA gene encoding the unique carbapenemases found in Bacteroides is restricted to division II Bacteroides fragilis strains. The aim of this study was to evaluate whether MALDI-TOF MS is suitable for differentiating B. fragilis strains which harbour the cfiA gene from those that do not. A well-defined collection of 40 B. fragilis isolates with known imipenem MICs (0.062->32 mg l-1) were selected for this study. Twelve B. fragilis strains with known cfiA status, including NCTC 9343 (division I) and TAL3636 (division II), were measured by means of microflex LT MALDI-TOF MS and well-defined differences in mass spectra between the cfiA-positive and cfiA-negative strains were found in the interval 4000-5500 Da. A further 28 strains were selected for the blind measurements: 9 cfiA-positive clinical isolates with different imipenem MICs ranging between 0.06 and >32 mg l-1 (different expressions of the metallo-b-lactamase gene) were clearly separated from the 19 cfiA-negative isolates. The presence or absence of the selected peaks in all tested strains clearly differentiated the strains belonging to B. fragilis division I (cfiA-negative) or division II (cfiA-positive). These results suggest a realistic method for differentiating division II B. fragilis strains (harbouring the cfiA gene) and to determine them at a species level at the same time. Although not all cfiA-positive B. fragilis strains are resistant to carbapenems, they all have the possibility of becoming resistant to this group of antibiotics by acquisition of an appropriate IS element for full expression of the cfiA gene, leading to possible treatment failure. © 2011 SGM Printed in Great Britain.